2020
DOI: 10.1177/2158244020919518
|View full text |Cite
|
Sign up to set email alerts
|

External Shocks, Institutional Quality, and Macroeconomic Performance in Nigeria

Abstract: The study examines the relative contributions of external shocks and institutional quality to macroeconomic performance in Nigeria, using Structural Vector Autoregressive (SVAR) approach. The study establishes the dominance of the relative contributions of external shocks measures over institutional quality to macroeconomic performance in the country. Even though the dominance of terms of trade and foreign aid is highlighted, the role of institutional quality is equally important as it also has significant pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…Prior studies had stirred a series of controversies among economists as to the necessity of stabilization policies needed to guarantee stable performance in key macroeconomic variables such as the GDP, unemployment, exchange rate, interest rate inflation rate and so on (Abere & Akinbobola, 2020). The monetarists led by Freedman postulate that an economy is usually stable so advocating for further stabilization policies is clearly unnecessary.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior studies had stirred a series of controversies among economists as to the necessity of stabilization policies needed to guarantee stable performance in key macroeconomic variables such as the GDP, unemployment, exchange rate, interest rate inflation rate and so on (Abere & Akinbobola, 2020). The monetarists led by Freedman postulate that an economy is usually stable so advocating for further stabilization policies is clearly unnecessary.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study builds on the foregoing studies on the relationship between macroeconomic shocks and employment, with focus on the influences of labour market institutions. In general, previous studies (e.g., Calderon et al 2012;Bluhm et al, 2020, Abere & Akinbobola, 2020 generally concluded that the quality of domestic institutions is as potent as the resilience of macroeconomic fundamentals in absorbing external shocks to output in the system. The main question in this regard is whether the labour markets also possess internal institutional mechanisms to aid efficient adjustment to shocks.…”
Section: Brief Review Of Literaturementioning
confidence: 97%
“…The ECMt−1 is a one lag error correction term that accounts for the speed of adjustment to the long-run equilibrium. 1 These may be the change in the time series due to some unique economic happenings that may have occurred as a result of changes economic policies,…”
Section: Model Specificationmentioning
confidence: 99%
“…Prior to the investigation of the long-run and short-run nexus between external economic shocks and monetary policy instruments, the unit properties of the series were examined using the Zivot-Andrew (1992) unit root test with structural breaks. 1 This is due to Engle and Granger (1987) claim that time-series data sets are not stationary; therefore, we need to check the stationarity of the series to avoid the spurious results obtained from the application of OLS method.…”
Section: Unit Root Test With Structural Breaksmentioning
confidence: 99%
See 1 more Smart Citation